Pengaruh Pembangunan Infrastruktur terhadap Pertumbuhan Ekonomi di Kalimantan Selatan - Winey, Apsiflaviana Riwut; Siregar, Syahrituah (PPJP ULM, 2019)
This study aims to determine how the influence of infrastructure development oneconomic growth in south Kalimantan and determine which infrastructure is mostinfluential on economic growth in south Kalimantan. Infrastructure as the productionfactor in this study is represented by road infrastructure, electricity infrastructure,and water infrastructure. At the same time, economic growth is characterized bygross regional income variables. This study uses panel data intending to get the BestLinear Unbiased Estimator results. The results show a Fixed Effect Model that bestfits the data conditions to help get the expected analysis results.This study's final results state that two of the three independent variablespositively and significantly affect the dependent variable. That two variables areelectricity infrastructure and water infrastructure. In contrast, the road infrastructurehas a positive effect but not significant on economic growth in South Kalimantan, andthe infrastructure that most influences economic growth is electricity infrastructure.